Difficulties in Conducting Short Horizon Event Studies: Call for Further Research - Jasmon, Abadan; Lai, Ming Ming; Ahamad, Abdul Aziz; Nik Salleh, Nik Mohamad Zaki (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
The wide variety of applications and the richness of data available have made event studies commonplace in economic, finance, and accounting research. The strength of the event study methodology is that abnormal returns due to a firm-specific, but time independent event may be precisely estimated by aggregating results over many firms experiencing a similar event at different times. The case study examines whether Malaysian GLC’s headline KPI announcements over the transformation period FY 2005-2014 resulted in significant abnormal stock returns. A pilot study using three-factor model of [4] showed that virtually all the significant abnormal stock returns were recorded in the first month following the announcement (short market reaction, i.e. short horizon).  However, since the company book values used in computing the HML proxy factor is only available at month-ends, the [4] model cannot be used for this short horizon study; even though R-squared increased due to additional proxy factors besides company beta, namely company size and growth. Thus, the actual study had to be conducted using a one-factor Short Horizon Event Study - the risk factor (beta) for each security is obtained through regression and then used to predict daily stock returns, and subsequently the abnormal returns, over a short horizon of 30 days’ post-announcement date.  Company size factor was controlled by grouping the securities according to small, medium, and large securities. Results showed that small and large securities consistently recorded abnormal stock returns.Overall, the study has demonstrated that over a short horizon, the stock value of GLCs can be increased through headline KPI announcements, thus reinforcing the signalling and agency theories. The more important contribution of this research is that it has highlighted deficiencies in the current model to study short horizon events, which hopefully will encourage more rigorous future research.